Analysis of heavy metals and inorganic element content in Stereospermum colais leaves (International Current Pharmaceutical Journal, 2013)
In the present study, the presence of heavy metals (Lead, Copper, Cadmium, Arsenic and Mercury) and inorganic elements (Sulphate, Fluoride, Chloride) were quantitatively estimated from the leaves of Stereospermum colais. Lead, Copper and Cadmium were analyzed using Atomic Absorption Spectrophotometry (AAS). Arsenic was estimated by colorimetric method. Mercury was estimated by cold vapour atomic absorption method. The qualitative analysis of inorganic elements was performed. Sulphate, fluoride and chloride were quantitatively estimated by turbidimetric, colorimetric and argentometric methods, respectively. The obtained results revealed that the content of heavy metals was within the permissible levels and hence the plant was safe to be utilized in herbal drug formulation.DOI: http://dx.doi.org/10.3329/icpj.v2i3.13583 International Current Pharmaceutical Journal, February 2013, 2(3): 63-66